Identification of a novel mutation in the CACNA1C gene in a Chinese family with autosomal dominant cerebellar ataxia - Chen, Jiajun; Sun, Yajuan; Liu, Xiaoyang; Li, Jia (BMC neurology, 2019)
Background Hereditary ataxia is a group of neurodegenerative diseases with progressive cerebellar ataxia of the gait and limbs as the main symptoms. The genetic patterns of the disease are diverse but it is mainly divided into autosomal dominant cerebellar ataxia (ADCA) and autosomal recessive cerebellar ataxia (ARCA), and about 45 pathogenic loci have been found in ADCA. The purpose of this study was to explore the genetic defect in a Chinese family with ADCA. Methods A three-generation Chinese family with ADCA was enrolled in this study, Exome sequencing was conducted in four family members, including the proband, and verified by Sanger sequencing. Results The rs779393130 mutation of the CACNA1C gene co-segregated with the ataxia phenotype in this family. The mutation was not detected in 50 unaffected controls. Conclusions The rs779393130 mutation of CACNA1C may be associated with the phenotype of the disease. The CACNA1C gene encodes the Cav1.2 (alpha-1) subunit of an L-type calcium channel and this subunit may be related to the ADCA phenotype. These findings may have implications for family clinical monitoring and genetic counseling and may also help in understanding pathogenesis of this disease.